Environmental and Sustainable Development in Islamic Perspective - Sabrina, R. (Budapest International Research and Critics University, 2020)
The development and preservation of the environment is a delamatic problem, as if there is some kind of complication between the objectives of development and the objectives of environmental preservation. This is because often factors (environmental kelastarian) are ignored / ignored in order to put forward the issue of national development which has more tangible benefits for the community. In order to overcome this problem, a sustainable and environmentally sound development agenda is needed, namely efforts to harmonize economic, social and environmental development. In economic, social and environmental development, Muslims have a strategic role because in Islam it has been regulated in the Quran, in Q. S 16:97, QS 2: 29, QS 6: 95, Q. S 6: 95, Q S 10: 6, QS 16,66,67,68 and Q; 27.28. In the use of natural resources, we must pay attention to ecological elements, care for nature and not cause damage to the earth. This is in line with the concept of sustainable development. Muslims must participate in spreading environmental values and practice them through various professions or positions that are carried by Islamic teachings. Meanwhile, to face global challenges, Muslims must learn science and technology, stop excessive environmental exploitation and the industrial world plays a role in overcoming environmental damage.